A study of hybrid seed corn pricing - Schwenneker, Brent (Kansas State University, 2008)
Hybrid seed corn pricing has increased significantly over the past six or seven years and continues to be a topic of conversation amongst farmers. This issue is also an area of concern for Monsanto. The hybrid corn pricing team at Monsanto is concerned that they price current products at a point to maximize profits while continuing to grow market share. The key is to price at a point that captures all the value of the differentiated products Monsanto offers. The objective for this study is to estimate a demand model for the hybrid seed corn industry. The demand model will allow us to look at many different aspects of the hybrid seed corn industry and also evaluate the own-price and cross-price elasticities. The own-price elasticity is especially important because it will be used to determine if current pricing is revenue or profit-maximizing. A hedonic pricing model was also estimated in this study to complement the demand model. It is important for Monsanto to understand what attributes or traits are significant in pricing and demand.
Keywords: Hybrid seed; Monsanto; Hedonic prices; Elasticity of demand; Economics, Agricultural (0503)